THE EFFECT OF A PSYCHOLOGICAL COUNSELING PROGRAM TO REDUCE ANXIETY AND PSYCHOLOGICAL STRESS AMONG FENCING PLAYERS BEFORE THE TOURNAMENT - Assist.prof.Dr. Sukaina Shaker Hassan (Proximus Journal Publishing, 2024)
The research aims to prepare a psychological counseling program for fencing players and to know the effect of the psychological counseling program in alleviating anxiety and psychological tension among the research sample. The hypothesis of the research has been the existence of statistically significant differences between the results of pre- and post-tests for both anxiety and psychological stress in the research sample. The research problem was to answer the following question: How much level do fencing players have of anxiety and psychological stress before the tournament? What is the impact of the psychological counseling program in alleviating anxiety and psychological tension among players? The research community was represented by the players of the sub-union of Diyala Club numbering (20) players, and the research sample has reached (10) players (4) players for the exploratory experiment has been excluded (6) players (2) players for lack of commitment to attend and (4) players for enjoying a low rate of anxiety and psychological tension and do not need the program. The extension sessions were applied by (16) sessions, three sessions per week and by (6) weeks, and then statistical means were extracted. The researcher reached a set of results, including: The results reached by the post-test proved that the percentage of anxiety and psychological tension has decreased compared to the results of the pre-test, and that the psychological counseling program prepared by the researcher has positively affected the mild anxiety and psychological tension among fencing players. The researcher has recommended emphasizing the role of the sports psychologist and a course in raising the level of the team and its progress, attention to the preparation of psychological counseling programs concerned with psychological variables such as fear, psychological pressure, and others, working to carry out a study similar to this study on individual and group games
Keywords: psychological counseling program; anxiety; stress